THE EDUCATIONAL ROBOTICS AS PART OF THE ENGINEERING EDUCATION - Natalia Tolstova; Denis A. Bondarenko; Konstantin Ganshin (Наука. Инновации. Технологии)
The problem of engineering and technical profile students training, the es-sence of the «educational robotics» concept are considered in the article. The didactic features of the use of educational robotics is represented. The organization of a pilot project in NCFU is described.